Constructive Leadership and Employee Innovative Behaviors: A Serial Mediation Model - Arasli, Huseyin; Arici, Hasan Evrim; Kole, Ezel (Mdpi, 2020)
This study aims to examine the influence of constructive leadership practices on the service innovative behaviors of hotel employees by a serial mediation system that treats employee psychological safety and employee creativity as mediators. Empirical data were collected from full-time frontline hotel employees in Antalya, Turkey. By using both convenience and judgmental sampling methods, this study included 357 hotel employees. The results provide empirical evidence for all suggested hypothesized associations. In particular, the findings display that psychological safety and engagement in creative work tasks play intervening roles (in the form of a chain) in the indirect influence of constructive leadership on employee perceptions regarding their service innovative culture. The current work provides practical contributions for hotel industry professionals who are in the treatment of implementing psychological safety and employee creativity, in order to establish innovative service culture in the hotel setting. The paper is among the first studies to investigate a serial mediation model to analyze which constructive leadership practices influence their innovative service culture.
Keywords: constructive leadership; safety; creativity; innovative behavior; hospitality industry; serial mediation